Исследование влияния плазменного воздействия на поверхностные свойства нетканых материалов на основе полилактида - Коржова, Алена Геннадьевна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
The effect of plasma on the surface properties of scaffolds based on polylactic acid is investigated. Elemental composition of the plasma modified scaffolds study by X-ray photoelectron spectroscopy. The content of nitrogen atoms on the sample surface varies from 8 to 11 % after argon and argon/diethylamine plasma. For samples treated with argon/diethylamine plasma, grafting of amino groups (up to 24 %) is observed.